Synthesis of 6-Chloro-5-(trifluoroacetyl)pyridine-3-carbonitrile: A Novel, Versatile Intermediate for the Synthesis of Trifluoromethylated Azaindazole Derivatives - Channapur, Manjunath B.; Hall, Roger G.; Kessabi, Jilali; Montgomery, Mark; Shyadligeri, Ashok S. (Synlett, 2019)
A synthesis of 6-chloro-5-(trifluoroacetyl)pyridine-3-carbonitrile, a versatile building block for the synthesis of trifluoromethylated N-heterocycles, is described. The reactions of 6-chloro-5-(trifluoroacetyl)pyridine-3-carbonitrile with 1,2- and 1,3-bisnucleophiles were investigated.
Keywords: pyridinecarbonitriles; pyrazolopyridines; trifluoromethylation; oxadiazoles; annulation